2013
DOI: 10.1111/j.1365-2265.2012.04518.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hypovitaminosis D with pharmacologic doses of cholecalciferol, oral vs intramuscular; an open labeled RCT

Abstract: Both regimens were considerably effective, safe and practical in treating hypovitaminosis D. Although we revealed superiority of oral route, at least at early short time, the way of treatment may depend on the patient's choice, compliance and availability of various forms of the drug in any regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 32 publications
3
22
0
1
Order By: Relevance
“…Other studies also found that accumulative doses of 1 00 000-1 20 000 IU/month were insufficient to raise serum-25(OH)D concentrations to ⩾ 75 nmol/l. 6,40 The study by Zabihiyeganeh et al, 6 showed that among Iranians (serum-25(OH)D o 75 nmol/l), 65.6% of the patients who received accumulative dose of 300 000 IU over 3 months reached serum-25(OH)D concentration ⩾ 75 nmol/l after 6 months, 6 a finding comparable to ours (66.7%). So, larger doses than monthly 1 00 000 IU are required to shift vitamin D status to ⩾ 75 nmol/l in the populations with high prevalence of vitamin D insufficiency.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Other studies also found that accumulative doses of 1 00 000-1 20 000 IU/month were insufficient to raise serum-25(OH)D concentrations to ⩾ 75 nmol/l. 6,40 The study by Zabihiyeganeh et al, 6 showed that among Iranians (serum-25(OH)D o 75 nmol/l), 65.6% of the patients who received accumulative dose of 300 000 IU over 3 months reached serum-25(OH)D concentration ⩾ 75 nmol/l after 6 months, 6 a finding comparable to ours (66.7%). So, larger doses than monthly 1 00 000 IU are required to shift vitamin D status to ⩾ 75 nmol/l in the populations with high prevalence of vitamin D insufficiency.…”
Section: Discussionsupporting
confidence: 85%
“…2 Concurrently, vitamin D deficiency/insufficiency is re-emerging as a worldwide public health issue. 3 Evidence shows that Middle Eastern women living in their home country [4][5][6] or in other countries as immigrants [7][8][9] have low serum-25(OH)D concentrations. Comparable to Turkish women, 45.0% of Iranian women living in Oslo, Norway, had serum levels o20 nmol/l.…”
Section: Introductionmentioning
confidence: 98%
“…Peak levels of 25OHD were seen at 30 and 120 days in those given oral and IM treatment, respectively. Another study in 92 adults with 25OHD <75 nmol/l compared 300,000 IU vitamin D 3 IM to 50,000 IU D 3 orally given on 6 occasions over 3 months [71] . A higher proportion of subjects receiving oral treatment had 25OHD >75 nmol/l at 3 and 6 months than IM subjects.…”
Section: Evidencementioning
confidence: 99%
“…demonstrated that considerable efficacy and safety of two different oral and injectable regimens utilizing a total dose of 300,000-IU Vitamin D3 in treating hypovitaminosis D.[18] They concluded that in the short-term oral preparations are effective in correction of Vitamin D deficiency. In our study too, the serum 25OHD levels at 6 weeks were comparable in the oral and IM D3 group.…”
Section: Discussionmentioning
confidence: 99%